Analysis Of The Influence Of Digital Marketing And Product Quality On Purchasing Decisions For 3second Products - Nia Sintiawati; Sri Murwanti (IQTISHADequity jurnal MANAJEMEN, 2023)
The purpose of this study was used to analyse whether digital marketing and product quality can influence consumer purchasing decisions on 3Second products in Solo Raya. This research is a quantitative study with non-probability sampling techniques with purposive sam-pling method where in this study not all members in the population can be used as samples, but there are several criteria used so that someone can be used as a sample. The number of samples in this study were 75 respondents. The results in this study indicate that digital marketing has no influence on consumer purchasing decisions, while product quality has a positive and significant influence on consumer purchasing decisions. It can be concluded that to increase the number of purchases, product quality must be improved while the digital marketing strategy must be done as attractively as possible so that it has an impact on consumer purchasing decisions.